The Problems of Learning Arabic through Google Classroom in Vocational High Schools During the Covid-19 Pandemic - Nur Laili Kholidatur Roihanah; Farikh Marzuqi Ammar (Indonesian Journal of Islamic Studies, 2022)
This study aims to find out the problems in learning Arabic through google classroom at SMK Muhammadiyah 2 Taman during the covid-19 pandemic. This study uses qualitative methods and uses research subjects from teachers and students of class IX at SMK Muhammadiyah 2 Taman. The results showed that during the pandemic, teachers used Google Classroom more often in learning Arabic. The problem with learning Arabic through Google Classroom is that it is difficult not to see students while learning because they are not face-to-face, limited data packages, student saturation and others.